Exploratory and Confirmatory Factor Analyses and Demographic Correlate Models of the Strategies for Weight Management Measure for Overweight or Obese Adults. Issue 4 (March 2015) - Kolodziejczyk, Julia K.; Norman, Gregory J.; Roesch, Scott C.; Rock, Cheryl L.; Arredondo, Elva M.; Madanat, Hala; Patrick, Kevin
Purpose: There is a need for a self-report measure that assesses use of recommended strategies related to weight management. Design: Cross-sectional analysis. Setting: Universities, community. Subjects: Exploratory factor analysis (EFA) involved data from 404 overweight/obese young adults (mean age = 22 years, 48% non-Hispanic white, 68% ethnic minority). Confirmatory factor analysis (CFA) involved data from 236 overweight/obese adults (mean age = 42 years, 63% non-Hispanic white, 84% ethnic minority). Measures: The Strategies for Weight Management (SWM) measure is a 35-item questionnaire that assesses use of recommended behavioral strategies for reducing energy intake and increasing energy expenditure in overweight/obese adults. Analysis: EFA and CFA were conducted on the SWM. Correlate models assessed the associations between SWM factor/total scores and demographics by using linear regressions. Results: EFA suggested a four-factor model: strategies categorized as targeting (1) energy intake, (2) energy expenditure, (3) self-monitoring, and (4) self-regulation. CFA indicated good model fit (χ 2 /df=2.0, comparative fit index = .90, standardized root mean square residual = .06, and root mean square error of approximation = .07, confidence interval = .06–.08, R 2 = .11–.74). The fourth factor had the lowest loadings, possibly because the items cover a wide domain. The final model included 20 items. Correlate models revealed weak associations between the SWM scores and age, gender, Hispanic ethnicity, and relationship status in both samples, with the models explaining only 1% to 8% of the variance (betas = –.04 to .29, p < .05). Conclusion: The SWM has promising psychometric qualities in two diverse samples.